Local versus landscape-scale determinants of nest-site selection in the Barbary Partridge Alectoris barbara. Issue 4 (2nd October 2018) - Hanane, Saâd
ABSTRACT: Capsule: Nest-site selection of Barbary Partridge Alectoris barbara in a Moroccan agroforestry system is dictated by nest scale rather than landscape-scale factors. Aims: To identify the most important factors affecting Barbary Partridge nest habitat selection in a Moroccan agroforestry landscape. Methods: I investigated the effect of two spatial scales (nest-site and landscape) on the probability of presence of nests. Topography, habitat structure, human disturbance and land-use parameters were measured at nests ( n  = 64) and random points ( n  = 64) within landscape plots (50 m radius) and nest-site plots (5 m). Results: At the nest scale, quadratic shrub cover and proximity to trees best explained nest habitat use. At the landscape scale, quadratic forest cover and linear distance to the nearest track positively influenced the nest presence probability. The most relevant scale was nest-scale followed by landscape scale. The variation partitioning analysis confirmed this spatial pattern. Conclusion: This approach was important to: (i) understand nest habitat use in the Barbary Partridge at nest and landscape scales, and (ii) highlight the most important variables driving habitat use in a Mediterranean agroforestry system. From a practical perspective, it is recommended to extend the same methodological approach to other Mediterranean agroforestry systems to find out if the species follows the same nest habitat selection pattern.